2016
DOI: 10.1007/s10461-016-1417-7
|View full text |Cite
|
Sign up to set email alerts
|

Can Short-Term Use of Electronic Patient Adherence Monitoring Devices Improve Adherence in Patients Failing Second-Line Antiretroviral Therapy? Evidence from a Pilot Study in Johannesburg, South Africa

Abstract: High levels of adherence are required to achieve the full benefit of ART. We assess the effectiveness of electronic adherence monitoring devices among patients failing second-line ART, as measured by viral load suppression. Cohort study of Wisepill™ real-time adherence monitoring in addition to intensified adherence counselling over 3 months in adults with a viral load ≥400 copies/ml on second-line ART in Johannesburg, South Africa between August 2013 and January 2014. Patients were sent SMS reminders upon mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…8, Of these 26 studies, 23 studies used SMS alone for reminders, and 3 used SMS plus counseling as noted in ►Table 1. Six reports were from the United States; [35][36][37][42][43][44] three each from Kenya 8,31,40 and South Africa; 28,39,48 two each from Uganda, 38,45 China, 34,47 and Cameroon; 30,41 and one each from Italy, 26 Brazil, 29 Nigeria, 32 New Zealand, 27 India, 33 Argentina, 46 Canada, 49 and Malaysia. 50 The types of studies included 19 RCTs, 8,27,[29][30][31][32][34][35][36]38,39,[41][42][43][44][45]47,50 three prospective cohort studies, 26,37,46 two ambidirectional studies (retrospective/prospective cohort study...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…8, Of these 26 studies, 23 studies used SMS alone for reminders, and 3 used SMS plus counseling as noted in ►Table 1. Six reports were from the United States; [35][36][37][42][43][44] three each from Kenya 8,31,40 and South Africa; 28,39,48 two each from Uganda, 38,45 China, 34,47 and Cameroon; 30,41 and one each from Italy, 26 Brazil, 29 Nigeria, 32 New Zealand, 27 India, 33 Argentina, 46 Canada, 49 and Malaysia. 50 The types of studies included 19 RCTs, 8,27,[29][30][31][32][34][35][36]38,39,[41][42][43][44][45]47,50 three prospective cohort studies, 26,37,46 two ambidirectional studies (retrospective/prospective cohort study...…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcomes addressed in the studies included one ART usage among study participants, 40 one adherence measured through prescription refills, 48 two viral load adherences, 37,46 six adherences over time, 31,33,34,38,39,43 and 16 self-reported adherences (►Table 2). 8,[26][27][28][29][30]32,35,36,41,42,44,45,47,49,50 Adherence interventions were measured as self-report, ART usage, adherence over time using a medication event monitoring system (MEMS) or an electronic adherence monitoring device, such as Wisepill, pharmacy refills, pill count, and clinical outcomes (viral load, HIV-ribonucleic acid [RNA] suppression, and cluster of differentiation 4 [CD4] count). Additionally, a summary of the outcome data, adherence assessment, metrics, relative effect (risk and odds ratios [OR]), and a measure of precision (95% confidence interval [CI]) for each study are shown in ►Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations